Screening of Accompanying First Degree Relatives of Patients with Primary Open Angle Glaucoma - Paudyal, Indira; Yadav, Roshan; Parajuli, Anil; Singh, Kalpana; Joshi, Prathibha Lama; Thapa, Suman (Nepalese Journal of Ophthalmology, 2022)
Introduction: Glaucoma is one of the common causes of blindness worldwide, and the leading cause of irreversible blindness .The overall prevalence of glaucoma in Nepal is 1.9%. Though poorly understood, primary open angle glaucoma (POAG) is believed to have a genetic or familial component that may occur through polygenic or multifactorial transmission. First-degree relatives of POAG patients have 4–16% risk of developing POAG. Given the circumstances and the prevalence of POAG in first degree relatives of POAG patients, screening the first degree relative/s accompanying the patient to the hospital can be a cost effective and viable tool for glaucoma screening that will not add any extra cost of travel and accommodation.Materials and methods: The authors performed a hospital-based cross-sectional study at a tertiary eye hospital in Nepal. All first-degree family members of POAG patients who accompanied them to the glaucoma clinic underwent a full ophthalmic examination.The optic disc was evaluated and intraocular pressure (IOP) was measured. POAG and glaucoma suspect were defined as per ISGEO classification.Results: Sixty one first degree relatives of 54 glaucoma patients were examined. The mean age was 30.67 years (±12.71). Fifty five(90.2%) of 61 of accompanying first degree relatives were off springs, 6 (9.8%) were siblings. Five out of 61 (8.2%) were diagnosed as glaucoma and started on anti-glaucoma medication. Fourteen participants (23%) were glaucoma suspects. Forty two (68.9%) of the participants had no sign of glaucoma.Conclusion: Ocular examination of the first-degree relatives accompanying POAG patients helped to identify a remarkable number of individuals with glaucoma and thus might be used as an effective and viable tool for screening glaucoma in a hospital setting. Awareness regarding glaucoma is very low even among the first degree relatives of glaucoma patients.